PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP KESULITAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2015) - Widya Wanti Paramastri; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the influence of corporate governance mechanism to financial distress. The dependent variable of this study is financial distress which is proxied as dummy variable of negative net profit in two years and the independent of this study are corporate governance index, institutional ownership, state ownership, and ownership concentration. Control variables in this study are return on sales, current ratio, book-to-market ratio, leverage and corporate size.The population of this study are manufacture companies that listed in Indonesia Stock Exchange (BEI) in 2014-2015. Total samples are 165 companies. This study used purposive sampling as the sampling method and logistic regression as the data analysis. In logistic regression the classical assumption test that needed in this analysis is multicollinearity test. The results of this study indicates that the corporate governance index has significant negatif influence to likelihood of financial distress. While the institutional ownership, state ownership, and ownership concentration have no significant influence to likelihood of financial distress.